A Model of Religious Moral Approach for Peatland Ecosystem Restoration in Indonesia - Gugah Praharawati; Fachruddin Majeri Mangunjaya; Hendra Maujana Saragih; Aos Yuli Firdaus; Taufik Mei Mulyana; Fauziah Ilmi; Muhammad Zulham; Haris Gunawan; Suwigya Utama; Ernawati Sinaga (Jurnal Manajemen Hutan Tropika, 2021)
Efforts to conserve peatlands and prevent forest fires are inseparable from human awareness and behavior. This study aims to find a model for a religious, moral approach by the clerics in supporting the implementation of peatland restoration. The study was carried out in designated Muslim locations with trained clerics. The farmers surveyed also have experienced by the Peatland Restoration Agency (BRG) programs: i.e., physical support, such as a canal dam program and demonstration plot of agriculture without burning (PLTB). The methods used combine quantitative surveys with a Likert scale to explore attitudes, subjective norms, perception, intention, and their impact on behavior. The results obtained show that the community religious leaders can be an important trigger in encouraging the movement. In the model, visible subjective norm (SN) variables contribute directly to intention by 23%. Perceived behavior control (PBC) directly has a positive and significant effect on intention 53% (p-value). This means the individual, in making a decision and intention to participate, is a factor that has a broad impact on the community and gives a positive value of 53% (good enough) on the intention. The individuals' decisions to participate in peatland conservation are prompted by perception of having a wide impact on the community.